SAT0213 IMPACT OF FLARES ON HEALTHCARE RESOURCE USAGE AND PROS IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS. (2nd June 2020) - Touma, Z.; Hoskin, B.; Atkinson, C.; Bell, D.; Massey, O.; Lofland, J. H.; Berry, P.; Karyekar, C.; Costenbader, K.
Abstract : Background: The effect of flares on healthcare resource usage and patient-reported outcome scores in SLE patients is not well quantified. Objectives: To understand how flares impact healthcare resource utilization (HCRU) and patient-reported outcomes amongst an international real-world dataset of SLE patients. Methods: The Adelphi Real World 2015 Lupus Disease Specific Programme (DSP) is a cross-sectional study of 263 rheumatologists in the US and EU5. Rheumatologists were asked to complete patient record forms (PRFs) for the next 5 prospectively consulting SLE patients; the same patients were asked to complete patient self-completion (PSC) forms describing how SLE affected them. PRFs collected data pertaining to the patient's diagnosis, disease history, current clinical outcomes, treatment and management history. PSCs collected similar data and included patient-reported outcome measures (PROs) to assess humanistic burden. Propensity score matching was used to assess differences in HCRU and health status between SLE patients who had flared (physician defined) in the last 12 months and those who had not. Matching variables were patient ethnicity, time since diagnosis, and severity at diagnosis. Data were extracted from 1278 PRFs, and 591 PSCs. Propensity score matching was carried out on two matched groups of 408 patients. Results: Demographic data are reported in Table 1 . Propensity score matching showed patients who flared in the last 12 months experienced significantly greater hospitalizations, visits to the ER, and total HCP consults in the last 12 months. Significantly greater drug burden lower physician and patient satisfaction, lower EQ-5D score (worse health status), lower FACIT Fatigue score (greater fatigue), and greater overall work impairment (Table 2 ) were also observed. Conclusion: The analysis of international real-world data confirmed that SLE patients who flared in the last year represent a greater burden on healthcare resource and demonstrate significantly worse health status, greater fatigue, lower patient and physician satisfaction and greater overall work impairment compared with non-flaring patients. There is a need for more effective treatments in this patient population to reduce patient and healthcare burden. Study funded by Johnson and Johnson. Disclosure of Interests: Zahi Touma Consultant of: Consultant for Janssen, Ben Hoskin Consultant of: Consultant for Janssen, Christian Atkinson Consultant of: Consultant for Janssen, David Bell Consultant of: Janssen, Olivia Massey Consultant of: Janssen, Jennifer H. Lofland Employee of: Janssen, Pamela Berry Employee of: Janssen, Chetan Karyekar Shareholder of: Johnson & Johnson, Consultant of: Janssen, Employee of: Janssen Global Services, LLC. Previously, Novartis, Bristol-Myers Squibb, and Abbott Labs., Karen Costenbader Grant/research support from: Merck, Consultant of: Astra-Zeneca